Bioinspired skin-like in vitro model for investigating catheter-related bloodstream infections - Majed Othman Althumayri; Azra Yaprak Tarman; Hatice Ceylan Koydemir (Scientific Reports, 2024)
Abstract Intravenous (IV) catheter-related bloodstream infections (CRBSIs) cause significant risks in healthcare, necessitating advancements in catheter design and materials. This study investigates the effectiveness of Ecoflex, a silicone-based material, in studying CRBSIs through the development of skin-like replicas that mimic human skin properties for use in wearable sensing devices. We characterized the replica’s bioinspired surface roughness, wettability, bacterial adhesion, and mechanical properties and validated its performance using in vitro IV simulation. The results demonstrated that the bioinspired model replicates human skin textures with less than 7.5% error for surface roughness ranging from 0.05 μm to 6.3 μm. Wettability tests revealed that the artificial sebum application significantly reduced the static contact angles for deionized water and artificial sweat. Comprehensive mechanical testing revealed material high elasticity and resilience, suitable for dynamic biomedical applications. Bacterial adhesion studies using Staphylococcus epidermidis showed varying adhesion patterns influenced by surface roughness, highlighting the potential for material texture to impact infection risk. In IV therapy simulations, we observed bacterial growth dynamics over the incubation period. Our findings suggest that Ecoflex-based skin-like replicas can serve as a valuable tool for developing and testing new catheters, while the potential for use in other medical innovation devices, including wearable sensing devices, ultimately contributes to improved patient outcomes and infection control strategies.